2019
DOI: 10.3390/jcm8111836
|View full text |Cite
|
Sign up to set email alerts
|

Better Myocardial Function in Aortic Stenosis with Low Left Ventricular Mass: A Mechanism of Protection against Heart Failure Regardless of Stenosis Severity?

Abstract: About one-tenth to one-third of patients with severe aortic stenosis (AS) do not develop left ventricular hypertrophy (LVH). Intriguingly, the absence of LVH despite severe AS is associated with lower prevalence of heart failure (HF), which challenges the classical notion of LVH as a beneficial compensatory response. Notably, the few studies that have attempted to characterize AS subjects with inadequately low left ventricular (LV) mass relative to LV afterload (i-lowLVM) described better prognosis and enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These observations were recently confirmed in an elegant longitudinal study by Ito et al [ 29 ], who observed gradually increasing cESS and falling mwFS in patients with EF < 60% and depressed LV contractility during the progression from moderate to severe AS, while mwFS was unchanged and cESS even slightly decreased over time (by about 6%) in those with EF ≥ 60%. Additionally, in our previous retrospective observational study of nondiabetic AS subjects, we have also reported no significant differences in cESS between moderate and severe AS with EF ≥ 50% [ 11 ]. Accordingly, cESS appears to be a controlled variable in AS subjects with preserved EF, including also P-LFLG-AS.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These observations were recently confirmed in an elegant longitudinal study by Ito et al [ 29 ], who observed gradually increasing cESS and falling mwFS in patients with EF < 60% and depressed LV contractility during the progression from moderate to severe AS, while mwFS was unchanged and cESS even slightly decreased over time (by about 6%) in those with EF ≥ 60%. Additionally, in our previous retrospective observational study of nondiabetic AS subjects, we have also reported no significant differences in cESS between moderate and severe AS with EF ≥ 50% [ 11 ]. Accordingly, cESS appears to be a controlled variable in AS subjects with preserved EF, including also P-LFLG-AS.…”
Section: Discussionmentioning
confidence: 83%
“…We retrospectively pre-screened the dataset of previously described patients with severe symptomatic degenerative AS (aortic valve area (AVA) index ≤ 0.6 cm 2 /m 2 by the continuity equation) and EF ≥ 50% without relevant coexistent diseases and concomitant abnormalities [ 10 , 11 ]. Beyond more than mild aortic regurgitation or disease of another valve, significant (≥50%) epicardial coronary narrowings, a history of acute coronary syndromes or coronary revascularization [ 10 , 11 ], exclusion criteria included any abnormalities which could potentially contribute to low SV index: atrial fibrillation, relevant mitral stenosis, mitral insufficiency or tricuspid regurgitation and right ventricular dysfunction [ 1 ]. We also excluded subjects with diabetes or chronic kidney disease because we had previously demonstrated subtle impairment of LV contractility in AS with concomitant type 2 diabetes [ 12 ] or renal dysfunction [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation